OPTIMALISASI PERAN PEMERINTAH KOTA SEMARANG DALAM MENGEMBANGKAN KAMPUNG BATIK SEMARANG - Hera Wisnu Murti; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
Batik is a national heritage (Indonesia) that has a high value and blend of art and is full of philosophical meanings. Batik is a craft that has become a distinctive Indonesian culture, in Semarang having its batik culture, Semarangan, which is a characteristic of Semarang City. The government made Semarangan batik a superior product because of its bright colors adopting typical Chinese and European styles and its motifs depicted the appearance of Semarang's distinctive features, such as Tugu Muda, Lawang Sewu, Blenduk Church, Pohon Asam, Blekok Srondol and others. In conducting this research the author uses a qualitative descriptive method, this study aims to find out what the role of the Semarang city government is in developing the Semarang Batik Village. Here researchers describe, record, analyze and interpret the conditions that occur in Batik Village today The results of the study show that in optimizing the role of government in developing Semarang Batik Village, represented by the Department of Industry, it has carried out enabling, enpowering and protecting efforts. To optimize the role of the government, optimization of third parties, from PT PLN, Bank of Central Java and USM in the form of CSR, guidance and training or facilitating exhibitions is needed. In its implementation in accordance with the existing indicators, it can be said that the government's role in developing Semarang Batik Village has been working as optimally as possible, but there are still some problems due to the lack of solid cooperation between related agencies or with third parties. In addition, there was a lack of good communication between the government and batik artisans, and a lack of response to the efforts made by the Semarang city government.Keywords: Batik, Semarang Batik Village, Community Empowerment.